Serum 25-hydroxyvitamin D level is associated with aortic distensibility and left ventricle hypertrophy in newly diagnosed type 2 diabetes mellitus. (November 2013) - Kuloğlu, Osman; Gür, Mustafa; Şeker, Taner; Kalkan, Gülhan Yüksel; Kırım, Sinan; Şahin, Durmuş Y; Harbalıoğlu, Hazar; Türkoğlu, Caner; Acele, Armağan; Elbasan, Zafer; Özaltun, Betül; Çaylı, Murat
We aimed to evaluate the association between serum vitamin D status and elastic properties of aorta in patients with diabetes mellitus (DM). We studied 136 patients with newly diagnosed DM (mean age: 62.9 ± 10.6 years). Serum 25-hydroxyvitamin D was measured using a direct competitive chemiluminescent immunoassay. Aortic distensibility was calculated from the echocardiographically derived ascending aorta diameters and haemodynamic pressure measurements. Left ventricle mass index (LVMI) was determined according to the Devereux formula. Multiple linear regression analysis showed that vitamin D level is independently associated with LVMI (β = −0.259, p = 0.001), aortic distensibility (β = 0.369, p < 0.001), high-sensitive C-reactive protein (hs-CRP) (β = −0.220, p = 0.002) and body mass index (β = −0.167, p = 0.015) in patients with DM. In diabetic patients, serum 25-hydroxyvitamin D level is independently associated with aortic distensibility. Vitamin D may play a role on pathogenesis of impaired elastic properties of aorta in type 2 DM.